2020
DOI: 10.1098/rsos.191542
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification performance of Pseudomonas fluorescens Z03 immobilized by graphene oxide-modified polyvinyl-alcohol and sodium alginate gel beads at low temperature

Abstract: 2020 Denitrification performance of Pseudomonas fluorescens Z03 immobilized by graphene oxidemodified polyvinyl-alcohol and sodium alginate gel beads at low temperature. R. Soc. open sci. 7: 191542. http://dx.Improving the effect of microbial denitrification under lowtemperature conditions has been a popular focus of research in recent years. In this study, graphene oxide (GO)-modified polyvinyl-alcohol (PVA) and sodium alginate (SA) (GO/PVA-SA) gel beads were used as a heterotrophic nitrification-aerobic deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…During the measurement, due to the electron beam passing through the sample, numerous cracks were formed on the surface of the film (Figure2C,G), allowing for the observation of the internal structure of the film. Figure 3 clearly shows that the internal structure of the film is porous; the resulting nanopores are most likely due to the presence of graphene oxide [43]. The surfaces of the obtained nanocomposites have a vesicular structure, which may be due to the fact that during nanoparticle generation, the alginate formed as nanocapsules with a size of about 20-50 nm (Figure 2B,F).…”
Section: Resultsmentioning
confidence: 98%
“…During the measurement, due to the electron beam passing through the sample, numerous cracks were formed on the surface of the film (Figure2C,G), allowing for the observation of the internal structure of the film. Figure 3 clearly shows that the internal structure of the film is porous; the resulting nanopores are most likely due to the presence of graphene oxide [43]. The surfaces of the obtained nanocomposites have a vesicular structure, which may be due to the fact that during nanoparticle generation, the alginate formed as nanocapsules with a size of about 20-50 nm (Figure 2B,F).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, these results 10. 3389/fmicb.2022.1037626 Frontiers in Microbiology 14 frontiersin.org also suggest that facultative anaerobic microorganisms capable of performing complete denitrification, such as P. aeruginosa, P. fluorescens, P. stutzeri, and P. denitrificans, could carry out the denitrification process at higher concentrations of DO, as demonstrated in a previous study, in which the authors showed that P. stutzeri isolated from a wastewater treatment system, can carry out nitrification and denitrification simultaneously in the presence of high levels of oxygen (bottles containing an atmosphere of 92% oxygen; Su et al, 2001;Liou and Madsen, 2008;Arat et al, 2015;Tang et al, 2020). This information coincides with the fact that Pseudomonas was the most abundant genus in this study (Figure 6C).…”
mentioning
confidence: 79%
“…Stepwise denitrification of NO 3 − to N 2 gas can be facilitated by other Pseudomonas strains such as P.aeruginosa [137], P. fluorescens [138], and P. denitrificans [139], which host all of the same denitrification genes as P.stutzeri. The two bacterial genera, Pseudomoas and Paracoccus, that include strains bearing all required genes to reduce NO 3 − to NO 2 − , NO and further to gaseous N 2 O and N 2 gasses are used to benchmark denitrification kinetics under different conditions [119,135].…”
Section: Microbial Nitrogen Metabolism and Biochemical Pathwaysmentioning
confidence: 99%